Sir Thomas Elyot as lexicographer - Stein, Gabriele (Oxford Univ. Press, 2014)
Sir Thomas Elyot's Latin-English dictionary, published in 1538, became the leading work of its kind in England. In this book Gabriele Stein describes this pioneering work, exploring its inner structure and workings, its impact on contemporary scholarship, and its later influence. The author opens with an account of Elyot's life and publications. Sir Thomas Elyot (c. 1490-1546) was a humanist scholar and intellectual ally of Sir Thomas More. He was employed by Thomas Cromwell in diplomatic and official capacities that did more to impoverish than enrich him, and he sought to increase his income with writing. His treatise on moral philosophy, 'The Boke named the Governour', was published in 1531 and dedicated to Henry VIII. His popular treatise on medicine, 'The Castell of Helth', went through seventeen editions. Professor Stein then considers how and why Elyot decided to compile a Latin-English dictionary. She looks at the guiding principles, the organization he devised, and the authors and texts he used as sources. She examines the book's importance for the historical study of English, noting the lexical regionalisms and items of vulgar usage in the Promptuorum parvulorum and the dictionaries of Palsgrave and Elyot, before discussing Elyot's linking of lemma and gloss, and use of generic reference points. She explains how Elyot translated and defined the Latin headwords and compares his practice with his predecessors. The author ends with a detailed assessment of Elyot's impact on sixteenth- and seventeenth century dictionaries and his place in Renaissance lexicography
Keywords: Elyot, Thomas -- Sir -- 1490?-1546; Elyot, Thomas